The Heavy Metal Pollution Index in Seawater of the Coastal Aquaculture Zone in Quang Ninh, Vietnam - Le Xuan Sinh; Le Van Nam; Nguyen Van Bach; Nguyen Thi Mai Luu; Do Manh Hao; Nguyen Thi Thu Ha (Research in Ecology, 2025)
Heavy metal pollution in coastal waters is on the rise, presenting serious threats to both ecosystems and human health. Coastal aquaculture zones, such as those in Quang Ninh province, are especially vulnerable due to the accumulation of heavy metals from multiple sources, including industrial wastewater, land runoff, and maritime activities. This study applies the Heavy Metal Pollution Index (HPI) to assess pollution levels based on the concentrations of nine heavy metals (Cr, Mn, Fe, Cu, Zn, As, Cd, Hg, Pb) found in seawater samples collected from coastal aquaculture areas in Quang Ninh. According to the HPI method, values exceeding 100 indicate polluted water, serving as a benchmark for evaluating heavy metal contamination in the region. A total of 25 seawater samples were collected and analyzed; of these, 18 samples (72%) had HPI values above 100, signaling a concerning level of heavy metal pollution, while only 7 samples (28%) fell below the threshold, suggesting no significant contamination. These results underscore the urgent need for enhanced monitoring of water quality and stricter regulation of pollution sources to protect both environmental and public health.